2023
DOI: 10.1162/edfp_a_00358
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Placement and Initial College Enrollment: Evidence from an Experiment

Abstract: To evaluate how Advanced Placement courses affect college-going, we randomly assigned the offer of enrollment into an AP science course to over 1,800 students in 23 schools that had not previously offered the course. We find no AP course effects on students’ college entrance exam scores (SAT/ACT). As expected, AP course-takers are substantially more likely to take the AP exam than their control group counterparts. At the same time, treatment group students opt out of the exam at very high rates and most do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Our results also underscore the complexities of policies that aim to accelerate students who are academically underprepared (e.g., Conger et al, 2020, 2021; Cortes et al, 2015; Hallett & Venegas, 2011; Jacob et al, 2017; Kolluri, 2018; McEachin et al, 2020; Troutman et al, 2018; Warne, 2017). Recent research from Texas found that college faculty concerned about the quality of high school DE courses wanted college credit to be tied to performance on a standardized final exam (Troutman et al, 2018).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…Our results also underscore the complexities of policies that aim to accelerate students who are academically underprepared (e.g., Conger et al, 2020, 2021; Cortes et al, 2015; Hallett & Venegas, 2011; Jacob et al, 2017; Kolluri, 2018; McEachin et al, 2020; Troutman et al, 2018; Warne, 2017). Recent research from Texas found that college faculty concerned about the quality of high school DE courses wanted college credit to be tied to performance on a standardized final exam (Troutman et al, 2018).…”
mentioning
confidence: 56%
“…Early exposure to advanced content that results in poor course performance may deter students from further study in related fields, working against the state’s goal to nudge students into high-demand occupations (Avery et al, 2018; Stinebrickner & Stinebrickner, 2013). On the other hand, students in the AP study also improved their science skills more than peers assigned to a non-AP class (Conger et al, 2020); and 11th-grade students in SDC College Algebra increased their enrollment (and success) in 12th-grade AP math courses, despite the low pass rates on this exam (Hemelt et al, 2020). Taken together, these findings crystalize the uncertainty that remains regarding the optimal components of high school dual-credit initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations